2010
DOI: 10.2174/138945010790711932
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Structure-Based Design of the Influenza A Neuraminidase Inhibitors

Abstract: Since 2003, highly pathogenic H5N1 influenza viruses have been the cause of large-scale death in poultry and the subsequent infection and death of over 140 humans. At present, there are only three licensed anti-Influenza drugs namely Relenza (Zanamivir - ZMV), Tamiflu (Oseltamivir - OTV) and Amantadine/Rimantadine. The latter targets the M2 ion channel whereas the other compounds target neuraminidase (NA) and were designed through structure-based enzyme inhibitor programmes. Some structural knowledge of the In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 0 publications
0
48
0
Order By: Relevance
“…Peramivir was briefly licensed for emergency use during the swine-origin H1N1 epidemic in an injectable formulation for patients on ventilators and is currently completing clinical trials, and several other backbones are being tested as well as further derivatives of zanamivir. Several recent reviews describe these new developments 3,5,6,6669 .…”
Section: Na Inhibitors and Resistance Mutationsmentioning
confidence: 99%
“…Peramivir was briefly licensed for emergency use during the swine-origin H1N1 epidemic in an injectable formulation for patients on ventilators and is currently completing clinical trials, and several other backbones are being tested as well as further derivatives of zanamivir. Several recent reviews describe these new developments 3,5,6,6669 .…”
Section: Na Inhibitors and Resistance Mutationsmentioning
confidence: 99%
“…The 'open' conformation of the crystal structure of H5N1 NA in complex with OTV (PDB ID: 2HU0) was used to rationalize the molecular mechanism of oseltamivir resistance using molecular docking simulations [4][5][6]. It was demonstrated that the 150-cavity can be exploited for designing the more potent inhibitors of H5N1 NA [4,7] in the same way as experimentally proposed [2].…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that the 150-cavity can be exploited for designing the more potent inhibitors of H5N1 NA [4,7] in the same way as experimentally proposed [2]. The relevance of these observations [4][5][6][7] was questioned by pointing out both that an improper initial structure (PDB ID: 2HU0) was used and that a 'closed' conformation of the N1:OTV co-crystal structure is more appropriate for such studies [8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations